Nietzsche's plan for political organization and its formation in political theory. - Dombowsky, Don. (University of Ottawa (Canada), 2001)
Virtually all treatments of Nietzsche's political thought today are concerned with its posthumous appropriation. The principal imperative guiding my work, conversely, is to situate Nietzsche's political thought in relation to the political issues, critiques and movements of his own period. I begin with a polemic of efforts in contemporary Anglo-American political philosophy to interpret Nietzsche's philosophy as essentially consonant with liberal democratic pluralism. In opposition to this view, I advance the proposition that the foundation of Nietzsche's political thought is the conservative or aristocratic liberal critique of democratic society found in Alexis de Tocqueville, Jacob Burckhardt and Hippolyte Taine. I subsequently demonstrate, however, that Nietzsche radicalizes this critique insofar as he takes as absolute what its proponents merely take for the potential dangers of democracy, advocating its subversion, containment or manipulation through the figures of the free spirits and the philosopher-legislators. I argue that Nietzsche is engaged in class warfare and that he is ultimately committed to the reversal of the process of democratization and the laying of the groundwork for an alternative aristocratic ideal of political organization which he sees as a condition for the production of the exemplary human being. I conclude that Nietzsche's radicalization of the aristocratic liberal critique is primarily informed by a reading of Machiavelli's The Prince which allows Nietzsche to think in terms of political control techniques and a spectral-syncretic or perspectival art of governance. Given this, I argue that Nietzsche's political thought may be more accurately situated in relation to the anti-liberal and anti-democratic neo-Machiavellian elite theorists of his generation like Vilfredo Pareto and Gaetano Mosca, and to the founders of mass psychology such as Gustave Le Bon. All continue the aristocratic liberal critique but radicalize it in supporting the idea of the manipulation of mass behavior through elite leadership. This conclusion is directed at those, in particular, who would argue that Nietzsche most closely resembles the anarchists of his period.
Keywords: Philosophy.